The effect of processing-based and output-based instruction on the acquisition of present simple tense of EFL learners - mahdi mardani; Alireza khoram (زبان پژوهی)
This study investigated the effects of processing-based instruction (PI) and output-based instruction (OI) on learners’ development in comprehension and production of the English present simple tense. The findings contribute to the ongoing debate on the effects of PI versus OI. Among 70 EFL learners at a private language center in Iran, 40 pre-intermediate learners were assigned to the PI group, and 20 learners were assigned to the OI group (n=20). The PI group received structured processing input activities, while the OI group engaged in structured output activities. Descriptive and analytical statistics revealed that participants in the PI group significantly outperformed the participants in the OI group in receptive knowledge of the target structure. However, both instructional methods affected the participants’ productive understanding of the present simple tense, and the difference between the efficacy of these two types of instruction on participants’ productive knowledge was not significant.